2000
DOI: 10.1111/j.1365-2141.2000.02349.x
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal venous thrombosis in neonates and infants: role of prothrombotic risk factors – a multicentre case–control study

Abstract: The factor V (FV) G1691A mutation, the prothrombin (PT) G20210A variant, the methylenetetrahydrofolate reductase (MTHFR) T677T genotype, together with fasting homocysteine (HCY) concentration, lipoprotein (Lp)(a), anti‐thrombin (AT), protein C (PC), protein S (PS) and anti‐cardiolipin antibodies were investigated in 65 consecutively recruited infants (neonate to < 12 months) with renal venous thrombosis (RVT; n = 31), portal vein thrombosis (PVT; n = 24) or hepatic vein thrombosis (HVT n = 10), and 100 age‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 28 publications
1
81
0
4
Order By: Relevance
“…Whereas congenital thrombophilia was described not to be associated with UVC thrombosis in one report (Turebylu et al 2007), Heller and colleagues published data from the childhood thrombophilia study group indicating an elevated odds ratio for the presence of congenital thrombophilia in neonates with renal, portal, or hepatic venous thrombosis (Heller et al 2000). A recent study confi rms a high prevalence of inherited thrombophilia in neonatal stroke (Suppiej et al 2007).…”
Section: Congenital Thrombophiliamentioning
confidence: 98%
“…Whereas congenital thrombophilia was described not to be associated with UVC thrombosis in one report (Turebylu et al 2007), Heller and colleagues published data from the childhood thrombophilia study group indicating an elevated odds ratio for the presence of congenital thrombophilia in neonates with renal, portal, or hepatic venous thrombosis (Heller et al 2000). A recent study confi rms a high prevalence of inherited thrombophilia in neonatal stroke (Suppiej et al 2007).…”
Section: Congenital Thrombophiliamentioning
confidence: 98%
“…Table 1 describes studies in the literature (between 2000 and 2013) that had reported cases of neonatal RVT with prothrombotic risk factors The presence of factor V Leiden mutation markedly increases the risk for renal vein thrombosis, particularly in neonates. Homozygosity is much rarer and is clinically associated with more severe thrombotic disease [11].…”
Section: Discussionmentioning
confidence: 99%
“…Heller et al [11] showed that non catheter-related abdominal thrombosis on neonates has a higher incidence of genetic prothrombotic risk factors. Some of these factors are genetic mutations of methylenetetrahydrofolate reductase (MTHFR-677 and MTHFR-1298), plasminogen activator inhibitor-1 4G/5G polymorphism and factor V Leiden mutation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Uttenreuther-Fischer et al identified 4.3% and Heller et al reported 4.2% pediatric portal vein thrombosis patients with hereditary protein C deficiency. [26][27] Seizes et al did not identify any patient with factor V leiden mutation out of total 20 EHPVO children they have studied. 28 According to Sharma et al factor V leiden and prothrombin gene mutations are infrequent in Indian patients with EHPVO.…”
Section: Resultsmentioning
confidence: 99%